Public Relations Management IAIN Bone in Disclosure of Information about Campus - Qudratullah Qudratullah (INJECT (Interdisciplinary Journal of Communication), 2022)
This research aims to explore the management of IAIN organizations Bone in disseminating information about the campus. Management needed to achieve goals in a measured manner so that they are not original just do it. But there is a map to reach the destination. These stages include planning, organizing, implementing and supervision. Need to dig deeper about management IAIN Bone organization in information disclosure to the public. This study uses a qualitative method. Research data collected through observation, interviews and documentation. Primary data taken from selected informants to explore organizational management in disseminating information about the campus. While the data secondary to previous literature-relevant literatures this research. The data is presented in descriptive analysis. Data collected was analyzed by reducing the data, then present it and finally draw conclusions. Research result shows that Planning for dissemination of IAIN Bone information carried out in a careful and gradual manner namely with editorial planning, design and working time and dissemination information. Organizing is done by dividing the work desk and duties to every human resource in it according to the potential and competence possessed. Implementation disseminating information in several media owned. In Among them are Instagram @ iainbone_ and Facebook fanpage with an account IAIN Bone and website with the address www.iain-bone.ac.id. Supervision conducted to evaluate the results of the performance that has been done. The goal is to improve information service systems to Public.